GREEN MARKETING : A REVIEW FROM ISLAMIC MARKETING ETHICS PERSPECTIVE - Susanti, Vitria (Universitas Islam Negeri Raden Intan Lampung, 2014)
Abstrak: Islam supports morality and matters that lead to a healthy society, and stands in the way against corruption andmatters that lead to it. The guiding principle for the behavior of a Muslim is A’milunSa’lihan - “Virtuous Deeds”. This term covers all deeds, not only acts of worship. The Guardian and Judge of all deeds is Allah (SWT) Himself. The most fundamental characteristics of a Muslim are piety and humility.Islamic Marketing Ethics (IME) that combines the principles of value maximization with the principles of equity and justice for the welfare is in accordance with the concept of green marketing. Although not mentioned specifically green marketing concept embodied in Islamic iMarketing Ethics. One of which is the value of social responsibility and value based marketing.Islamic Marketing Ethics requires fair and justice practice not only between the producer and concumer but also from all the stakeholder to be resposible to the society and environtmernt. Keywords : green marketing, islamic marketing and ethics perspective